Potensi Cendawan Endofit dari Bunga Bawang Dayak untuk Menekan Pertumbuhan Ralstonia solanacearum pada Tanaman Tomat - Putri Wulan Cahyani; Noor Laili Aziza; Yusriadi Marsuni (Universitas Lambung Mangkurat, 2021)
Cultivation of tomato plants (Lycopesicum esculentum Mill.) Is often exposed to plant diseases. One of the diseases that often attacks tomato plants is bacterial wilt disease caused by R. solanacearum. Therefore, it is necessary to have biological control with the application of an antagonistic agent, namely the provision of endophytic fungi from dayak onion flowers. This study aims to determine the types of endophytic fungi in dayak onion flowers and to determine the potential of endophytic fungi in suppressing the growth of R. solanacearum. This research was conducted from February to May 2020, taking samples of dayak onion flowers in the Experimental Field of the Faculty of Agriculture and samples of symptomatic tomato plants on the Karang Anyar Farmer Group's land then continued with isolation, purification, identification, and antagonistic testing at the Production Laboratory of the Faculty of Agriculture, Lambung Mangkurat University, Banjarbaru. The method used in this study was a one-factor completely randomized design (CRD) with nine treatments, namely C1 = endophytic fungi A + R. solanacearum, C2 = endophytic fungi B + R. solanacearum, C3 = endophytic fungi F + R. solanacearum, C4 = endophytic fungi G + R. solanacearum, C5 = endophytic fungi I + R. solanacearum, C6 = endophytic fungi J + R. solanacearum, C7 = endophytic fungi K + R. solanacearum, C8 = fungi endophytic N + R. solanacearum, and C9 = endophytic fungi P + R. solanacearum and repeated three times. This study used a comparison, namely control with three replications, in order to obtain 30 experimental units. The results of this study that endophytic fungi from dayak onion flowers have the potential to suppress the growth of R. solanacearum. Based on the research, there were 17 endophytic fungi from dayak onion flowers with nine endophytic fungi which had the fastest growth rate of radius. Fungi with the genus Colletotrichum sp., Mucor sp., and Papulaspora sp. has the potential to suppress the growth of R. solanacearum with moderate to strong percentage of inhibition.